ANALYSIS OF CHARACTERISTICS OF PHYLLANTHUS ACIDUS ELECTROLYTE SOLUTION AS A RENEWABLE ENERGY SOURCE - Lubis, Khairiah (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2022)
Research has been conducted which aims to: (i) produce a characterization device for Phyllanthus acidus electrolyte solution, (ii) to determine the characterization of a Phyllanthus acidus electrolyte solution. The method used is an experimental laboratory method. In this study electrolyte solutions were used which were produced from all types of cermai fruit (Phyllanthus acidus). Electrode pair variations are Cu-Zn, Cu-Al, and Cu-Pb. Variations in the volume of the solution 100, 200, 300 ml. Variations in distances of 2, 4 and 6 cm. NaCl addition concentration variations were 1.67%, 3.33%, 5.00%, 6.67%, 8.33% and 10.00%. The measurement results are the voltage and current that are tabulated and analyzed. In this study to determine the effect of adding volume using a distance of 2 cm with electrodes Cu-Zn, Cu-Al, and Cu-Pb. Measurement to determine the effect of the electrode distance is to use a 300 ml volume with Cu-Zn, Cu-Al, and Cu-Pb electrodes. Meanwhile, to determine the effect of increasing the concentration of NaCl to the solution using a 300 ml volume with a distance of 2 cm electrode and the electrode pairs Cu-Zn, Cu-Al, and Cu-Pb. From the results of research conducted the characterization device of Phyllanthus acidus electrolyte solution has been successfully made with good performance. Referring to the results and analysis as a whole, it is found that changes in volume, variation in distance, and addition of NaCl concentration give different values of current strength and voltage as well as different conductivity and solids of solutes. However, the effect of pH on increasing the volume of solution and adding NaCl tends to maintain its pH. At the addition of the volume of the solution there is a linear relationship between the addition of volume to the output electricity ie the greater the volume of the electrolyte solution of Phyllanthus acidus fruit is used, the higher the electric power produced. Whereas in electrode distance testing there is an inverse relationship between the electrode distance with the output voltage and electric current ie the closer the electrode distance the greater the value of the current and voltage produced, conversely the farther the distance between the electrodes the smaller the value of the voltage and electrical output. Likewise with the addition of NaCl concentration into the solution, the greater the concentration of NaCl the greater the voltage and current or the value of the electrical output and the greater the conductivity and solute solids in the solution. In this study, Cu-Zn electrodes are the best electrodes in producing electrical output values compared to Cu-Al and Cu-Pb electrodes.